Antimicrobial activity of the edible mushroom Pleurotus eryngii (DC.) Quél grown in liquid medium (Acta Scientiarum. Biological Sciences, 2021)
Edible mushrooms have a number of medicinal properties and this study aimed to investigate the antimicrobial activity of Pleurotus eryngii DPUA1816 in metabolic broths after being grown in submerged cultivation. Mycelial fragments of pure P. eryngii culture was inoculated in sweet potato culture medium and incubated at 150 rpm for 15 days at 25°C. Pleurotus eryngii was also cultivated for 18 days under the same conditions, the mycelial biomass was separated by filtration for quantification. The supernatant was used in the diffusion test in agar and performed against Escherichia coli CCCD-E005, Staphylococcus aureus CCCD-S009, Pseudomonas aeruginosa CCCD-P004, Candida albicans CCCD-CC001, Candida parapsilosis CCCD-CC004 and Candida tropicalis CCCD-CC002. The samples showed no inhibitory activity against bacteria, however they showed some activity against C. albicans (12.17 mm), C. parapsilosis (27.67 mm) and C. tropicalis (13.67 mm). After being cultivated for 18 days, P. eryngii was able to inhibit all yeasts after 12 days of culture, with an inhibition halo of 29.33 mm at 16 days against C. parapsilosis. This study demonstrates the antifungal potential filtered liquids from P. eryngii cultivated in purple-skinned sweet potato culture medium, which suggests the possibility of the use of this species by the pharmaceutical industry as a natural source of biological action.